No B.S. direct marketing : the ultimate, no holds barred, kick butt, take no prisoners direct marketing for non-direct marketing businesses / Dan S Kennedy - Kennedy, Dan S.Author
A guide to direct marketing for non-direct marketing businesses. It helps readers learn how they can use high-profile techniques, such as mail-order and television tactics, to their small business and achieve results. It also includes an audio CD featuring interviews and discussions with a team of consultants